the The Effectiveness Of Spiritual Qurâanic Emotional Freedom Technique (SQEFT) Intervence Against The Change Of Brief Psychiatric Rating Scale (BPRS) On Patient With Schizophrenia - Rosyanti, Lilin (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Dimension of spiritual nursing demands the role of nurse in order to give holistic treatment, combine physical, psychological, social, and spiritual dimension. The psychospiritual intervention : SQEFT is intervention of psychospiritual combination that combines between spiritual Qurâanic therapy and psychological therapy of EFT, as additional spiritual intervention for patient with schizophrenia by not reducing any medical treatment program that the patient does.  The objective of this research,  in order to examine the influence of  SQEFT Intervence Against The Change Of BPRS On Patient With Schizophrenia. Method, there were 7 mental patients skizoprenia  participate of this research.  who were diagnosed schizophrenia with psychiatry of DSM-IV-TR by psychiatric doctor with preliminary BPRS value scale in less than 60.  Research Result,  the result test of bonferroni showed that three groups had significant difference. There was a significant difference between non SQFET and SQEFT1,SQEFT2 with P value â¤  0,000. This difference showed that BPRS value moved lower significantly before being given SQEFT intervention, after being given SQEFT in stage 1 and SQEFT in stage 2. BPRS value that was lower showed psychological condition, schizophrenia patientâs cognitive condition which were better.